Fabrication of Immobilized Eggshell/TiO2 Photocatalytic Composite-based Membrane - Haikal Hafiy Abdul Kadir; Ungku Nor Akmal Ungku Mohd Abdullah; Zarul Haziq Muhammad; Dzinun, Hazlini (Multidisciplinary Applied Research and Innovation, 2024)
The use of synthetic dyes presents serious environmental consequences, including pollution, health risks, and the presence of toxic chemicals in food and food products. Methylene blue, a cationic dye commonly found in wastewater, poses health hazards due to its blue solution and potential adverse effects on human well-being. To address these issues, heterogeneous photocatalysis offers a greener approach to treating textile wastewater by employing environmentally friendly oxidants. In this study, the focus is on the removal of methylene blue (MB) using a photocatalyst composed of eggshell/TiO2 composites. These composites were synthesized by calcining eggshells to produce calcium oxide (CaO) and then combining them with TiO2. Testing was conducted using 1 g of prepared samples and a 4 ppm MB solution as a model pollutant to assess the removal percentage. Among the three different ratios 9:1, 7:3 and 5:5 of eggshell/TiO2, the eggshell/TiO2 composite with a ratio of 9:1 demonstrated optimal performance, achieving the highest MB removal around 63.89% whereby this performance is significant with 100% TiO2 (0:10). Provenly, eggshells possess excellent adsorbent properties and act as effective support for TiO2 in the composite photocatalyst. The increased surface area of the eggshell/TiO2 composite photocatalyst enhances both MB solution adsorption and photocatalytic degradation, thereby improving its overall effectiveness. In conclusion, eggshells show great potential as a support material for photocatalysts, making them an environmentally friendly catalyst option.